If it's not what You are looking for type in the equation solver your own equation and let us solve it.
32=7(x)-3(x)
We move all terms to the left:
32-(7(x)-3(x))=0
We add all the numbers together, and all the variables
-(+4x)+32=0
We get rid of parentheses
-4x+32=0
We move all terms containing x to the left, all other terms to the right
-4x=-32
x=-32/-4
x=+8
| -t²+17t+60=0 | | 3h=h=40/3 | | 2r+-11=-3 | | 73=x+82 | | (2x-6)=(4x-12) | | -4+5n-2n=-24 | | -162+5x+4x=54 | | .75(3x-2)+4x=11 | | 6x+8(2-x)=12 | | -14j=392 | | 10w-5+17=-8 | | -4q+-3=9 | | .5(9x-2)+3x=59 | | m/3+1=3.3 | | -1/4x-5=10+1x | | 6x+2x+10x=180 | | 30+6n=11n | | 8x+3x-2=31 | | 9x=27=3 | | -9(x+13)+4x=48 | | -6=h/3-8 | | -59(x+9)=-5 | | r|-29=-41 | | nX40=4 | | (6x-2)+(11-9)+30=180 | | 1227(z+8)–5(6+z)=48 | | -3(x+10)+6x=-12 | | (15x-3)+(5x+63)=180 | | 12=x+21 | | 4-(3x-6)-8x=2x-(-x+4) | | 6x-9+8x-2=-81 | | 13.6=≤3.9p |